Multilayer polyimide film as well as preparation method and application thereof

By introducing silicon-containing monomers and large volume monomers into the PI film, and adding SiO2 aerogel intermediate layer to regulate the molecular structure and add inorganic fillers, the problem of insufficient thermal stability of PI films in flexible PI plate applications is solved. A multi-layer polyimide film with low dielectric constant and high thermal stability is achieved, meeting the needs of high-performance insulating materials in the microelectronics industry.

CN119391017AActive Publication Date: 2025-02-07GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202411491625.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing PI films are not thermally stable enough in flexible PI board applications and cannot meet the requirements of the microelectronics industry for high-performance insulating materials.

Method used

Through molecular structure design, silicon-containing monomers and large volume monomers are introduced to copolymerize with BPDA and ODA to form low dielectric polyimides, and the SiO2 aerogel intermediate layer is added through physical modification to regulate the molecular structure and add inorganic fillers. Reduce dielectric constant and improve thermal stability.

Benefits of technology

The prepared multi-layer low-dielectric polyimide film has low dielectric constant, high temperature resistance, high interface compatibility and low water absorption rate, which meets the requirements of flexible PI boards for stability and durability, and has a wide range of application prospects. In the field of microelectronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391017A_ABST
    Figure CN119391017A_ABST
Patent Text Reader

Abstract

The invention discloses a multilayer polyimide film as well as a preparation method and application thereof, belongs to the technical field of high-performance polyimide, and solves the problem that the thermal stability is not ideal when a PI film is applied to a flexible PI plate in the prior art. The method comprises the following steps: mixing ODA, GAPD and DMAc in an ice bath, mixing BPDA and TAHQ, and adding the mixture in batches to obtain a solution B; adding SiO2 aerogel into absolute ethyl alcohol, and carrying out ultrasonic treatment at room temperature to obtain a solution C; coating the solution B into a film shape, drying, coating the solution C on the film, drying, coating the solution B on the film again, and drying to obtain the polyimide film. The multilayer low-dielectric polyimide film prepared by the invention has the advantages of low dielectric, high temperature resistance, high interface compatibility and low water absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-performance polyimide, and more specifically to a multilayer polyimide film and a preparation method and application thereof. Background Art

[0002] Polyimide (PI) is a polymer material with excellent thermal stability, mechanical stability, chemical stability and electrical insulation properties. Due to these characteristics, PI has become one of the most important polymer interlayer insulating materials in the microelectronics industry. However, with the development of integrated circuits, device size continues to decrease, and device integration continues to increase. Traditional aromatic PI films cannot meet the requirements of the microelectronics industry for high-performance insulating materials because their dielectric constant (Dk) and dielectric loss (Df) are not low enough. Especially in the field of 5G high-frequency communications and flexible printed circuit boards (FPCB), the demand for low dielectric constant materials is particularly urgent. Therefore, reducing the dielectric constant and dielectric loss of PI films has become a research focus.

[0003] Low dielectric materials are materials with a dielectric constant less than 3. The application of low dielectric materials is mainly to solve the problems of RC delay, crosstalk and increased power consumption caused by parasitic capacitance between lines and layers of ultra-large-scale integrated circuits. However, in the application of flexible PI boards, the thermal stability of existing PI films is not ideal. Summary of the invention

[0004] The present invention provides a multilayer polyimide film and a preparation method and application thereof, which are used to solve the problem in the prior art that the thermal stability of the PI film is not ideal when it is applied to a flexible PI board.

[0005] In a first aspect, the present invention provides a method for preparing a multilayer polyimide film, comprising the following steps: stirring 4,4'-diaminodiphenyl ether, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethylacetamide in an ice bath to obtain a solution A; mixing biphenyltetracarboxylic acid dianhydride and p-phenylene-diphenyltrimethylol dianhydride, adding them to the solution A in multiple times, and mixing them evenly to obtain a solution B; adding a hydrophilic SiO2 aerogel to anhydrous ethanol, and ultrasonicating at room temperature to obtain a solution C; coating the solution B into a film, and sequentially performing drying, thermal cyclization in an inert atmosphere, and UV curing operations to obtain a first film; coating the solution C on the first film, and drying to obtain a second film; coating the solution B on the second film, and sequentially performing drying and thermal cyclization in an inert atmosphere to obtain the multilayer polyimide film.

[0006] As a possible implementation method, the amount ratio of the biphenyltetracarboxylic acid dianhydride, the p-phenylene-diphenyl trimellitic acid dianhydride, the 4,4'-diaminodiphenyl ether and the 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 5:5:7-9:1-3; and / or, the mass fraction of the hydrophilic SiO2 aerogel is 10%-20%; and / or, the solution B is coated into a thin film with a coating amount of 20-30 μL / cm 2 ; and / or, coating the solution C on the first film in an amount of 20 to 30 μL / cm 2 ; and / or, coating the solution B on the second film in an amount of 20 to 30 μL / cm 2 .

[0007] As a possible implementation, the adding into the solution A in multiple times is 2 to 4 times, each time interval is 30 to 60 minutes; and / or, the mixing is uniform to obtain solution B, the mixing temperature is 20 to 25°C, and the mixing time is 8 to 12 hours; and / or, the drying temperature is 70 to 80°C, and the drying time is 1 to 2 hours; and / or, the inert atmosphere environment is a nitrogen environment; and / or, the conditions of the thermal cyclization are: heating to 100, 150, 200, 250, and 300°C at a heating rate of 2 to 5°C / min, respectively, and keeping warm at each temperature for 60 to 80 minutes.

[0008] In a second aspect, the present invention provides a multilayer polyimide film, which is prepared according to the preparation method described in any possible implementation manner of the first aspect.

[0009] As a possible implementation, under the condition of 1 MHz, the dielectric constant is 2 to 3.

[0010] As a possible implementation, the thickness is 10 to 20 μm.

[0011] In a third aspect, the present invention provides an application of a multilayer polyimide film prepared by the preparation method described in any possible implementation of the first aspect or a multilayer polyimide film described in any possible implementation of the second aspect in a flexible polyimide board.

[0012] In a fourth aspect, the working temperature of the flexible polyimide board is 25-450°C.

[0013] The present invention introduces silicon-containing monomers (GAPD, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane) and bulky monomers (TAHQ, p-phenylene-diphenyl trimellitic acid dianhydride) and copolymerizes with BPDA (biphenyltetracarboxylic acid dianhydride) and ODA (4,4'-diaminodiphenyl ether) to form low-dielectric polyimide through molecular structure design. By introducing low-polarity chemical bonds, the molecular polarity and electronic polarization are effectively reduced, thereby reducing the dielectric constant. By adding a SiO2 aerogel interlayer through physical modification, since the dielectric constant of air is extremely low (about 1), the introduction of pores in PI can greatly reduce the number of polarized molecules per unit volume, thereby reducing its overall dielectric constant. By regulating the molecular structure and adding inorganic fillers to adjust the dielectric properties of polyimide, a low-dielectric polyimide with excellent thermal stability is obtained to meet the requirements of flexible PI boards for stability and durability, so that it has broad application prospects in the field of microelectronics.

[0014] The multilayer low dielectric polyimide film prepared by the present invention has the advantages of low dielectric, high temperature resistance, high interface compatibility and low water absorption. The inorganic filler SiO2 aerogel of the second layer is evenly dispersed in the system without agglomeration. The low dielectric polyimide film with a sandwich structure does not have a stratification phenomenon, indicating that the film has excellent interface compatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 This is a morphological diagram of a polyimide film provided in an embodiment of the present invention, wherein A is polyimide film I and B is polyimide film V.

[0017] Figure 2 The dielectric constant test results of the polyimide film provided in the embodiment of the present invention.

[0018] Figure 3 This is the FT-IR characterization result of the polyimide film provided in the embodiment of the present invention.

[0019] Figure 4 This is the TGA characterization result of the polyimide film provided in the embodiment of the present invention.

[0020] Figure 5 The interface compatibility test results of the polyimide film I provided in the embodiment of the present invention, wherein A is before peeling and B is after peeling. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In order to solve the problem that the thermal stability of PI film in the prior art is not ideal when it is applied to flexible PI board, the embodiment of the present invention provides a preparation experiment of multilayer polyimide film. Figure 1 It can be seen that the embodiment of the present invention successfully produced a multilayer polyimide film.

[0023] Furthermore, the performance of the multilayer polyimide film prepared in the embodiment of the present invention is characterized, and it is known that the multilayer polyimide film prepared in the embodiment of the present invention has a dielectric constant of 2 to 3, has Si-O-Si and Si-C bonds in the molecule, and has better thermal stability.

[0024] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0025] Example 1

[0026] This embodiment provides an experiment for preparing a multilayer polyimide film.

[0027] 4,4'-diaminodiphenyl ether (ODA), 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane (GAPD) and dimethylacetamide (DMAc) were stirred in an ice bath for 1 hour to obtain solution A-Ⅰ; biphenyltetracarboxylic acid dianhydride (BPDA) and p-phenylene-triphenylene dianhydride (TAHQ) were mixed and added to solution A-Ⅰ three times with an interval of 30 minutes each time, and mixed evenly to obtain solution B-Ⅰ; wherein the molar ratio of BPDA, TAHQ, ODA and GAPD was 5:5:7:3, and a hydrophilic SiO2 aerogel with a mass fraction of 10% was added to anhydrous ethyl acetate. The mixture was stirred in 5% paraformaldehyde solution and then subjected to ultrasonic treatment at room temperature to obtain solution C-Ⅰ; 100 μL of solution B-Ⅰ was taken with a pipette and coated on a clean glass sheet of 2 cm×2 cm, and after being coated into a thin film, it was dried, thermally cyclized under a nitrogen environment, and light-cured in an ultraviolet UV machine to obtain a first film-Ⅰ; 100 μL of solution C-Ⅰ was taken with a pipette and coated on the first film-Ⅰ, and dried to obtain a second film-Ⅰ; 100 μL of solution B-Ⅰ was taken and coated on the second film-Ⅰ, and after drying and thermally cyclized under a nitrogen environment, it was immersed in deionized water at 100°C, removed from the glass sheet, and dried in an oven at 100°C to obtain a polyimide film-Ⅰ.

[0028] ODA, GAPD and DMAc were stirred in an ice bath for 1 hour to obtain solution A-Ⅱ; BPDA and TAHQ were mixed and added to solution A-Ⅱ three times with an interval of 30 minutes each time, and mixed evenly to obtain solution B-Ⅱ; wherein the molar ratio of BPDA, TAHQ, ODA and GAPD was 5:5:7:3, 10% hydrophilic SiO2 aerogel was added to anhydrous ethanol, and solution C-Ⅱ was obtained by ultrasonication at room temperature; 100 μL solution B-Ⅱ was taken with a pipette and coated on 2 cm ×2cm clean glass sheet, coated into a thin film, and then dried, thermally cyclized in a nitrogen environment, and light-cured in an ultraviolet UV machine to obtain the first film-Ⅱ; 150μL of solution C-Ⅱ was aspirated with a pipette and coated on the first film-Ⅱ, and dried to obtain the second film-Ⅱ; 100μL of solution B-Ⅱ was aspirated and coated on the second film-Ⅱ, and then dried, thermally cyclized in a nitrogen environment, and then immersed in 100℃ deionized water, removed from the glass sheet, and dried in a 100℃ oven to obtain a polyimide film-Ⅱ.

[0029] ODA, GAPD and DMAc were stirred in an ice bath for 1 hour to obtain solution A-Ⅲ; BPDA and TAHQ were mixed and added to solution A-Ⅲ three times with an interval of 30 minutes each time, and mixed evenly to obtain solution B-Ⅲ; wherein the molar ratio of BPDA, TAHQ, ODA and GAPD was 5:5:7:3, 10% hydrophilic SiO2 aerogel was added to anhydrous ethanol, and solution C-Ⅲ was obtained by ultrasonication at room temperature; 100 μL of solution B-Ⅲ was taken with a pipette and coated on 2 cm ×2cm clean glass sheet, coated into a thin film, and then dried, thermally cyclized in a nitrogen environment, and light-cured in an ultraviolet UV machine to obtain the first film-Ⅲ; 200μL of solution C-Ⅲ was aspirated with a pipette and coated on the first film-Ⅲ, and dried to obtain the second film-Ⅲ; 100μL of solution B-Ⅲ was aspirated and coated on the second film-Ⅲ, and then dried, thermally cyclized in a nitrogen environment, and then immersed in 100℃ deionized water, removed from the glass sheet, and dried in a 100℃ oven to obtain a polyimide film III.

[0030] ODA, GAPD and DMAc were stirred in an ice bath for 1 hour to obtain solution A-IV; BPDA and TAHQ were mixed and added to solution A-IV three times with an interval of 30 minutes each time, and mixed evenly to obtain solution B-IV; wherein the molar ratio of BPDA, TAHQ, ODA and GAPD was 5:5:7:3, 10% hydrophilic SiO2 aerogel was added to anhydrous ethanol, and solution C-IV was obtained by ultrasonication at room temperature; 100 μL of solution B-IV was taken with a pipette and coated on 2 cm ×2cm clean glass sheet, coated into a thin film, and then dried, thermally cyclized in a nitrogen environment, and light-cured in an ultraviolet UV machine to obtain the first film-Ⅳ; 250μL of solution C-Ⅳ was aspirated with a pipette and coated on the first film-Ⅳ, and dried to obtain the second film-Ⅳ; 100μL of solution B-Ⅳ was aspirated and coated on the second film-Ⅳ, and then dried, thermally cyclized in a nitrogen environment, and then immersed in 100℃ deionized water, removed from the glass sheet, and dried in a 100℃ oven to obtain a polyimide film-Ⅳ.

[0031] Taking kapton polyimide film as a comparison, its preparation process is as follows: add 10 mol of 4,4'-diaminodiphenyl ether (ODA) and N,N-dimethylacetamide (DMAc) into a 500 mL round-bottom flask, stir in an ice bath for 1 hour, then add 10 mL of pyromellitic dianhydride (PMDA) in batches, react at room temperature for 12 hours, and then perform drying and thermal cyclization operations under a nitrogen environment in sequence, soak in 100°C deionized water, remove from the glass slide, and dry in a 100°C oven to obtain polyimide film V.

[0032] Example 2

[0033] This embodiment provides a performance characterization experiment of a multilayer polyimide film.

[0034] The morphology of the polyimide film I and the polyimide film V prepared in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that due to the addition of SiO2 aerogel, the polyimide film I has a matte surface and the SiO2 aerogel is evenly distributed in the film without agglomeration and phase separation.

[0035] The dielectric constants of the polyimide films I to V prepared in Example 1 were tested respectively. The test conditions were: film thickness 10 μm, length and width 2 cm×2 cm, frequency 10 2 ~10 7 Hz, the temperature is room temperature. Figure 2 The results shown by Figure 2 It can be seen that due to the large number of CC and CH bonds contained in GAPD, which are groups with low molecular polarizability, the introduction of GAPD can hinder the accumulation of polymer chain segments, reduce molecular polarization, thereby increasing the free volume, forming a dielectric confinement effect, and reducing the dielectric constant of polyimide (PI). At the same time, the introduction of silicon-oxygen bonds can increase the flexibility of the PI molecular structure. By introducing the large-volume monomer TAHQ, the distance between polymer molecular chains can be effectively increased, the interaction force between molecules can be reduced, and the close stacking of molecular chains can be reduced. Such structural changes lead to an increase in the free volume inside the material, reducing the number of polarized molecules per unit volume, and thus reducing the dielectric constant of the material.

[0036] By physically modifying and adding a SiO2 aerogel interlayer, since the dielectric constant of air is extremely low (about 1), introducing pores into PI can greatly reduce the number of polarized molecules per unit volume, thereby reducing its overall dielectric constant.

[0037] The polyimide films I to V prepared in Example 1 were characterized by FT-IR respectively, under the following conditions: ATR infrared, film thickness of 10 μm, length and width of 2 cm×2 cm, and room temperature. Figure 3 The results shown by Figure 3 It can be seen that the C=O bond is at 720cm -1 There is a bending vibration peak at 1368cm -1 The stretching vibration peak appears at 1780 cm -1 and 1720cm -1 The stretching vibration peak at 1490 cm -1 and 3095cm -1There are characteristic absorption peaks of CC bond and hydrocarbon CH bond stretching at 764 cm -1 、1056cm -1 The stretching vibration peaks of Si-C and Si-O-Si bonds can be observed at 2941 cm -1 The stretching vibration peak of the CH bond can be seen at , and the results show that GAPD is successfully introduced into the PI molecular structure.

[0038] Example 3

[0039] This embodiment provides an experiment for testing the water absorption performance of a multi-layer polyimide film.

[0040] The polyimide films I to V prepared in Example 1 were tested for water absorption performance, respectively, under the following test conditions: room temperature, immersion time in water for 48 hours, film thickness of 10 μm, length and width of 2 cm×2 cm, respectively. The results shown in Table 1 were obtained.

[0041] Table 1 Water absorption test results of polyimide film

[0042] Before water absorption / g After water absorption / g Polyimide film Ⅰ 0.0025 0.0026 Polyimide film Ⅱ 0.0055 0.0055 Polyimide film Ⅲ 0.0039 0.0040 Polyimide film Ⅳ 0.0022 0.0023 Polyimide film Ⅴ 0.0031 0.0026

[0043] As can be seen from Table 1, compared with polyimide film V, the water absorption of polyimide film I to polyimide film IV is significantly lower. Compared with polyimide film V, although polyimide film I to polyimide film IV have a lower glass transition temperature (Tg, 285°C), they have low water absorption and excellent hydrolysis resistance. Low water absorption is conducive to the reduction of dielectric constant. PMDA and GAPD monomers are highly active, resulting in easy explosion and polymerization of the reaction, and a decrease in molecular weight. Therefore, the present invention selects BPDA anhydride as the preparation raw material.

[0044] Example 4

[0045] This embodiment provides a thermal stability test experiment of a multilayer polyimide film.

[0046] The polyimide films I to V prepared in Example 1 were characterized by TGA (thermogravimetric analysis) under the following conditions: the temperature range was from room temperature to 900° C. and the atmosphere was nitrogen. Figure 4 Results shown.

[0047] Depend on Figure 4It can be seen that the silicon-containing monomer GAPD is an aliphatic diamine, and it does not have a rigid structure with high temperature stability such as a benzene ring. The number of benzene rings in the molecular chain is reduced. Due to the high flexibility of the alkyl chain, the flexibility of the polymer main chain is increased, and the high temperature stability of the PI film gradually decreases. Although the addition of GAPD will reduce the high temperature stability, no obvious degradation will occur at temperatures below 450°C. Since the polyimide film V itself has excellent thermal stability, and the thermal stability of polyimide films I to IV is not much different from that of polyimide films I to IV, they also have excellent thermal stability. The material for welding the circuit board is tin-lead alloy, and the welding temperature is about 250°C, so it meets the welding requirements.

[0048] Example 5

[0049] This embodiment provides an interface compatibility test experiment of a multilayer polyimide film.

[0050] This was done by quickly peeling off the 3M pressure-sensitive tape attached to the sample. Figure 5 Results shown.

[0051] Depend on Figure 5 It can be seen that there is no obvious delamination of the substrate before and after the 3M pressure-sensitive adhesive is peeled off. In the use of flexible electronic devices, the adhesion between substrates is crucial. This shows that polyimide film I has excellent interfacial compatibility.

[0052] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0053] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a multilayer polyimide film, characterized in that: The following steps are involved: 4,4'-diaminodiphenyl ether, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethylacetamide were stirred in an ice bath to obtain a solution A; Mix biphenyltetracarboxylic acid dianhydride and p-phenylene-diphenyltrimethylol dianhydride, add them to the solution A in multiple times, and mix them evenly to obtain solution B; The hydrophilic SiO2 aerogel was added into anhydrous ethanol and subjected to ultrasonic treatment at room temperature to obtain solution C; The solution B is coated into a thin film, and then dried, thermally cyclized in an inert atmosphere, and UV-cured to obtain a first thin film; Applying the solution C on the first film and drying to obtain a second film; The solution B is coated on the second film, and drying and thermal cyclization operations are performed in sequence under an inert atmosphere to obtain the multilayer polyimide film.

2. The method according to claim 1, characterized in that: The molar ratio of the biphenyltetracarboxylic acid dianhydride, the p-phenylene-diphenyltrimethylol dianhydride, the 4,4'-diaminodiphenyl ether and the 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 5:5:7-9:1-3; And / or, the mass fraction of the hydrophilic SiO2 aerogel is 10% to 20%; And / or, the solution B is coated into a thin film with a coating amount of 20 to 30 μL / cm 2 ; And / or, the solution C is coated on the first film in an amount of 20 to 30 μL / cm 2 ; And / or, the solution B is coated on the second film in an amount of 20 to 30 μL / cm 2 .

3. The method according to claim 1, characterized in that The adding into the solution A in multiple times is 2 to 4 times, each time interval is 30 to 60 minutes; And / or, the mixing is uniform to obtain solution B, the mixing temperature is 20-25° C., and the mixing time is 8-12 h; And / or, the drying temperature is 70-80° C., and the drying time is 1-2 hours; And / or, the inert atmosphere environment is a nitrogen environment; And / or, the conditions for the thermal cyclization are: heating to 100, 150, 200, 250, 300° C. at a heating rate of 2-5° C. / min, respectively, and keeping at each temperature for 60-80 min.

4. A multilayer polyimide film, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 3.

5. The multilayer polyimide film according to claim 4, characterized in that: At 1MHz, its dielectric constant is 2 to 3.

6. The multilayer polyimide film according to claim 4, characterized in that: Its thickness is 10 to 20 μm.

7. Use of the multilayer polyimide film prepared by the preparation method according to any one of claims 1 to 3 or the multilayer polyimide film according to claims 4 to 6 in a flexible polyimide board.

8. The use according to claim 7, characterized in that: The working temperature of the flexible polyimide plate is 25-450°C.

Citation Information

Patent Citations

  • Preparation method of high performance and low thermal expansion coefficient polyimide film

    CN107286653A

  • Ultrathin polyimide film and preparation method thereof

    CN116238220A

  • Flexible polyimide film

    CN118725567A

  • Double-sided metal clad laminate and fabrication method thereof

    US20100035066A1

Cited By

  • Multilayer low-dielectric photosensitive polyimide as well as preparation method and application thereof

    CN120623483A

  • Multilayer low dielectric photosensitive polyimide and preparation method and application thereof

    CN120623483B

  • High-temperature-resistant high-airtightness polyimide composite film and preparation method thereof

    CN120985850A